MEMBANGUN KOMITMEN ORGANISASI MELALUI MOTIVASI KERJA DAN BUDAYA ORGANISASI: STUDI PADA KARYAWAN MASJID NAMIRA LAMONGAN: MEMBANGUN KOMITMEN ORGANISASI MELALUI MOTIVASI KERJA DAN BUDAYA ORGANISASI: STUDI PADA KARYAWAN MASJID NAMIRA LAMONGAN - Rudi Wibowo; Erna Nur Faizah; Nuning Nurna Dewi (Institut Agama Islam Sumatera Barat Pariaman, 2026)
This research is motivated by the importance of organizational commitment in improving organizational performance and sustainability, especially in religious-based organizations such as mosques, where employees are still found to have less than optimal commitment due to a lack of work motivation and organizational culture support. This study aims to analyze the influence of work motivation and organizational culture on organizational commitment among employees of the Namira Mosque in Lamongan. The research method used is a quantitative approach with multiple linear regression analysis techniques. The population in this study were all 45 employees of the Namira Mosque in Lamongan with a sampling technique using total sampling. Data collection was carried out through questionnaires that had been tested for validity and reliability. The results of the study indicate that work motivation and organizational culture have a positive and significant effect on organizational commitment, both partially and simultaneously. The R Square value is 0.961 or 96.1%. Organizational culture has a more dominant influence than work motivation. The coefficient of determination value shows that both variables are able to explain most of the variation in organizational commitment. The conclusion of this study confirms that increasing work motivation and implementing a positive organizational culture consistently can strengthen employee commitment to the organization.